Linear Video Games in the Context of Player Immersion - Pigulak, Joanna (Replay. The Polish Journal of Game Studies, 2019)
The paper aims to outline features of linear video games in context of a player immersion. The first part of the paper deals with a brief introduction concerning the characteristic of linear narrations, especially its character-centric specifics and the using of non-interactive cutscenes. In the second part of the paper, the author analyzes the selected linear game and indicates how video games’ developers design gameplay in order to involve players in narration. The author examines a hypothesis that using non-interactive scenes stimulate player’s immersion and develop narrations in linear video games.